Preoperative Diagnosis of Xanthogranulomatous Pyelonephritis - Afgan, Farah; Mumtaz, Seemal; Ather, M Hammad (Urology Journal, 2009)
Introduction: The aim of this study was to evaluate the possibility of differentiating xanthogranulomatous pyelonephritis (XGPN) preoperatively from chronic pyelonephritis on the basis of demographic data, clinical parameters, and biochemical, microbiological, and radiological workups. Materials and Methods: Between 1995 and 2005, a total of 239 patients were diagnosed to have pyelonephritis at our center, of which, 56 underwent nephrectomy. Forty-five (80.4%) of the nephrectomy specimens showed diagnosis of chronic pyelonephritis and 11 (19.6%) showed XGPN. Results: Compared to chronic pyelonephritis, XGPN was more likely to occur in the middle-aged women (90.9%) with diabetes mellitus (63.6%). A positive history of UTI was more frequent in these patients, too. The disease was likely to present with flank pain and tenderness in 100.0% and 90.9% of the patients with XGPN, respectively. Anemia (81.8%), hematuria (81.8%), and bacteriuria (90.9%) were more frequent in these patients than in those with chronic pyelonephritis. The mean blood hemoglobin was 7.0 g/dL in the patients with XGPN. Proteus mirabilis was detected in 6 patients (54.5%) of the XGPN group and only 2 of the chronic pyelonephritis group (P < .001). Renomegaly and kidney calculus were more frequently noted in the patients with XGPN. Finally, XGPN led to a higher rate of postoperative complications. Conclusion: Demographic data, comorbidities, predisposing factors, and biochemical as well as roentgenological features are significant but nonspecific indicators of preoperative diagnosis of XGPN.